Reading « Hairstories » and « Hairitages » in Léonora Miano’s and Rokhaya Diallo’s Works - Montlouis-Gabriel, Johanna (Études littéraires africaines, 2019)
Cet article vise à analyser un symbole qui distingue les femmes afro-descendantes : leur chevelure crépue. Ces dix dernières années, denombreuses afro-féministes (aux États-Unis, en France, dans la Caraïbe et ailleurs) ont repris possession de leurs cheveux comme partie essentielle de leur héritage et ont choisi de garder leur état naturel, souvent surnommé « nappy » (contraction de l’anglais « natural » et « happy »). Dans notre analyse, nous comparerons les approches de l’écrivaine Léonora Miano et celles de l’activiste Rokhaya Diallo telles qu’elles apparaissent dans leurs oeuvres respectives, à savoir le roman Blues pour Élise et la nouvelle « Corpus Christi » pour la première et le roman graphique Pari(s) d’amies ! pour la seconde. Dans leurs oeuvres, Léonora Miano et Rokhaya Diallo souhaitent déconstruire les discours et les représentations négatives des cheveux et du physique des afro-descendantes, en revendiquant l’amour de soi. Bien que certains personnages résistent à l’idée du cheveu naturel, nous verrons que cette réappropriation constitue un acte performatif.
http://www.apela.fr/
Keywords: afro-féminisme; amour de soi; approches et analyses; arts; cheveux; discipline; femmes* afro-descendantes; féminisme africain; féminisme afroaméricain; littérature; performance; périodes historiques; ressource en ligne; réappropriation; études littéraires

Je sais pourquoi chante l'oiseau en cage - Angelou, Maya; Besse, Christiane (Librairie générale française, 2012)
« Dans ce récit, considéré aujourd'hui comme un classique de la littérature américaine, Maya Angelou relate son parcours hors du commun, ses débuts d'écrivain et de militante dans l'Amérique des années 1960 marquée par le racisme anti-Noir, ses combats, ses amours. Son témoignage dénué de la moindre complaisance, révèle une personnalité exemplaire. À la lire, on mesure mieux encore le chemin parcouru par la société américaine en moins d'un demi-siècle. »– Quatrième de couverture.
Section: 345 pages ; 18 cm. Traduction de I know why the caged bird sings.
Keywords: 1900-1999; afro-féminisme; amériques; antiracisme; approches et analyses; arts; biographie; cours; discipline; féminisme afroaméricain; lit2815; premier cycle; périodes historiques; racisme; régions géographiques; systèmes d'oppressions; thématiques; écriture des femmes*; états-unis; études littéraires

Life notations of Daisy Sweeney: Reflections of othermothering, musicianship and Montreal - Campbell, Arlene (Université York, 2012)
The life story of Mrs. Daisy Sweeney, an African Canadian native of Montreal, Quebec, helps fill a void in the historical documentation of Montreal Blacks (especially female elders). Of particular significance is her prominence as a music educator and othermother during her life. The current literature on African Canadian othermothering experiences is not synonymous with both White or African American females and inclusion of their voices in academic, as well as mainstream spaces, is virtually non-existent. This dissertation asks: What did it mean to be a first generation 'Negro' working class bilingual female in a largely hostile White francophone Quebec metropolis in the early 20th Century? How can her narratives help shape and inform life history and African Canadian othermothering research? My sojourn with Mrs. Daisy Sweeney referenced African centered epistemology in my conceptual understanding of herself and community mothering. Capturing her conversations meant engaging with multiple methodologies articulated through African oral traditions, life history, archival canons and interdisciplinary inquiries. It is striking to note that there were not only certain tensions associated with memory loss and physical limitations (prompted by the aging process) that destabilized and enriched our 'interactive' communication, but also revealed a rupture and reversal of the participant/researcher dynamic. In spite of blatant racial discrimination that plagued Montreal's Black communities during that time, Daisy Sweeney fulfilled a life-long dream and taught hundreds of children the canon of classical piano for over 50 years. She lived her voice through her music, finding ways to validate her own identity and empowering others in the process. She used the musical stage as her platform to draw invaluable connections between race, gender, language and social class. Daisy Sweeney's generation of othermothers is dying out and, as the carriers of culture, the urgency to tell their stories must be emphasized. The account respects, reclaims and reflects those voices. It is time to write in African Canadian female elders and diversify the exclusionary genre of life history and archival research.
http://hdl.handle.net/10315/31697
Keywords: 1900-1999; DIG; afro-féminisme; amériques; approches et analyses; discipline; femmes* noires; histoire et politique; maternité; montréal; musique; mémoires/thèses; philosophie; périodes historiques; québec; racisme; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; travail

Representing the Black female subject in western art - Nelson, Charmaine (Routledge, 2010)
Nelson analyzes not only how, where, why and by whom black female subjects have been represented in Western art, but also what the social and cultural impacts of the colonial legacy of racialized Western representation have been. She poses questions about the concepts of production, the consequences of comsumption and more
Disponible en ligne: https://doi-org.proxy.bibliotheques.uqam.ca/10.4324/9780203851241 Contenu: Through an-other's eyes : white Canadian artists – Black female subjects – Racing childhood : representations of black girls in Canadian art – Slavery, portraiture, and the colonial limits of Canadian art history – The fruits of resistance : reading portrait of a Negro slave on the sly – Tying the knot : Black female slave dress in Canada – Coloured nude : fetishization, disguise, dichotomy – The "hottentot venus" in Canada : modernism, censorship, and the racial limits of female sexuality – White marble, Black bodies, and the fear of the invisible Negro : – Signifying blackness in mid-nineteenth-century neoclassical sculpture – Vénus Africaine : race, beauty, and African-ness – Allegory, race, and the four continents : Jean-Baptiste Carpeaux's les quatre parties du monde soutenant la sphere céleste – Conclusion : whiteness as collective narcissism, towards a new vision.
Keywords: afro-féminisme; approches et analyses; arts; cours; discipline; féminisme afroaméricain; har4610; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; racisme; représentation des femme*; représentation des femmes* racisées; ressource en ligne; système colonial; systèmes d'oppressions; thématiques

Decoding Black Women: Policing Practices and Rape Prosecution on the Streets of Philadelphia - Irving, Toni (NWSA Journal, 2008)
Black women are generally displaced as victims of rape. The police response to the sexual assault of black women in general and lower-class black women in particular is illustrative of how sexual ideologies help construct complex social hierarchies that in turn structure rights. How the law currently deals with rape places black women outside of the narrative frames that legitimate entitlement. Rape continues to stand in for, and effectively obscure, other social, political, and economic concerns. Unpublished and often ignored, the rape narrative is a ripe site to supply oppositional interpretations of national experience and transmit some of the structural problems in the criminal justice system. Pulling from over two thousand “real” rape cases of low-income black women ignored and not investigated in Philadelphia between 1995 and 2000, this article reads black female rape narratives as case studies in order to discuss the way personal narratives of rape victims are structured by competing and overwhelming sociolegal narratives that undercut their reception. As the fastest growing prison population, the presence of the law to punish black women stands in stark contrast to the absence of the law to protect them.
Keywords: 1900-1999; 1990-1999; afro-féminisme; amériques; approches et analyses; arts; corps; cours; discipline; droit; droit des femmes* noires; droits des femmes*; féminisme afroaméricain; histoire et politique; intersectionnalité; inégalités; philadelphie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; science politique; science politique et droit; sex2283; sexisme; systèmes d'oppressions; thématiques; viol; violences; états-unis; études littéraires

The master’s tools will never dismantle the master’s house - Lorde, Audre (Sister outsider: essays and speeches, 2007)
Première édition: 1984
Keywords: afro-féminisme; amériques; approches et analyses; arts; corps; cours; discipline; fem3600; féminisme afroaméricain; histoire et politique; lesbianisme; militance; premier cycle; régions géographiques; thématiques; émotions; états-unis; études littéraires

The art of history African American women artists engage the past - Collins, Lisa Gail (Rutgers University., 2002)
In this lively and engaging book, Lisa Gail Collins examines the work of contemporary African American women artists. Her study comes at a time when an unprecedented number of these artists-photographers, filmmakers, painters, installation and mixed-media artists-have garnered the attention and imagination of the art-viewing public. To better understand the significance of this particular historical moment in American visual arts, Collins focuses on four "problems" that recur when these artists confront their histories: the documentation of truth; the status of the black female body; the relationship between art and cultural contact and change; and the relationship between art and black girlhood. By examining the social and cultural histories which African American women artists engage, Collins illuminates a dialogue between past and present imagemakers. The Art of History is a major contribution to the study of American visual culture. It will be of use to both scholars and students in art history, African American studies, American studies, and women's studies.
Keywords: afro-féminisme; amériques; approches et analyses; arts visuels et médiatiques; corps; cours; discipline; fem1000; femmes* afro-américaines; féminisme afroaméricain; féminismes noirs; pratiques féministes; premier cycle; régions géographiques; thématiques; états-unis